Additively manufactured mechanical metamaterials based on triply periodic minimal surfaces: Performance, challenges, and application. Issue 26 (26th October 2022) - Sharma, Deepak; Hiremath, Somashekhar S.
Abstract: Lattice structures with architecture based on triply periodic minimal surfaces (TPMS) have recently attracted much attention due to their mathematically controlled topologies, which give rise to predefined and fascinating mechanical properties. Such materials with topology-dependent properties are generally known as "metamaterials." The research on the TPMS-based metamaterials was restricted to theoretical knowledge until the recent development of additive manufacturing technology (AM). Herein, the design, properties, challenges, and applications, of TPMS-based mechanical metamaterials are reviewed. This review provides the researcher with a collective resource of numerical and experimental data for the AM of TPMS-based structures.